Implementasi Metode SMARTER Untuk Rekomendasi Penerima Bantuan Raskin Masa Covid 19 - Julfikar Rahmad; Volvo Sihombing; Masrizal Masrizal (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
The problem of poverty is a classic problem that occurs in every country, both developed countries and developing countries like Indonesia. In every country, there are many programs carried out by the government to overcome the problem of poverty, one of which is the RASKIN program carried out by the Indonesian government. The method used to complete this research is SMARTER (Simple Multi Attribute Rating Technique Exploiting Ranks). During the Covid 19 pandemin, which is currently happening, various kinds of assistance are needed for middle and lower class people in rural areas, thus to distribute assistance, assistance distribution techniques are needed so that it reaches the right people. The SMARTER method was chosen because it is a form of decision support model used in decision making with multi attributes that will be used to solve decision-making problems. The research was conducted in Sei Beluru Village, Meranti District, Asahan Regency. In Sei Beluru Village, several criteria were obtained from direct observation of the field, namely the area of the house floor, the type of floor of the house, the type of house wall, the toilet facilities, the source of drinking water, lighting, materials. fuel used, frequency of eating, ability to buy meat, ability to buy clothes, ability to seek treatment, monthly income, education of the head of household, ownership of assets. Decision support systems using the Smarter method are able to analyze data on people who are entitled to receive Raskin assistance. The results obtained from this study are that from several prospective recipients of Raskin assistance with the specified criteria, it is found that the most prioritized alternative has the highest value of 0.603 using the Smarter method.